Shaking the table : survival and healing amongst identity center practitioners - Rivera, Stephanie Hernandez; McElderry, Jonathan A. (Identity & practice in higher education-student affairs., 2025)
Shaking the Table provides perspectives and narratives of practitioners working in, or who have worked in, identity centers. Colleges and universities across the country continue to grapple with supporting students in their marginalized identities, including gender, race, ethnicity, sexual identity, ability, socioeconomic status, religious identity, and citizenship status. The creation of spaces and centers to support students in their acclimation, belonging, and identity development has been one way institutions have sought to address the needs of those with marginalized identities. Those working within these spaces have provided students with transformative learning and developmental experiences. Despite this contribution to campus equity and inclusion efforts, the voices and experiences of those engaged in this work are often invisible. In the face of increasing resistance to equity and inclusion work nationally, and the multiple demands placed on the staff in these spaces, it is crucial to center and uplift these voices that are often relegated to the margins. This book features first-person accounts of the complexities, challenges, joy, and resistance practitioners experience while surviving and healing through and from this work. Shaking the Table is a resource of guidance, wisdom, connection, and community for those who share in this labor and who aspire to do this work. It is also a call to action for colleagues, supervisors, and institutional leaders to better understand, champion, and uplift those working in these spaces.